Noninvasive cardiac output monitoring system based on photoplethysmography - Can Wang; Chao Huang; Shuming Ye (2014 IEEE International Conference on Progress in Informatics and Computing, 2014)
Cardiac output (CO) is the key indicator of the state of cardiac function. To realize noninvasive, continuous, portable, reproducible cardiac output monitoring, we design a cardiac output monitoring system based on photoplethysmography(PPG) which is stable, non-invasive and convenient to collect. K-calibration algorithm is used in the software part of this system. The main idea of K-calibration algorithm is to calibrate the constant K value on the basis of the relationship between the stroke volume (SV) and PPG from invasive SV, then combine the K value and the noninvasive PPG to calculate the SV, and calculate CO from SV. We collect the invasive SV by FloTrac / Vigileo monitor, and at the same time collect the PPG signals and some other parameters, then combine the calibrated K value and PPG to calculate SV. After making a correlation analysis with the calculated SV and the invasive SV, the result shows that they have a good correlation with each other. Making a comparison between the continuous CO collected by our designed monitoring system in real time and the invasive CO collected by the FloTrac / Vigileo monitoring system will be our follow-up job. And the achievement can be used in mobile or wearable instrument.